Mapping Regions Within Cosmopolitan Inversion In(3R)Payne Associated With Natural Variation in Body Size in Drosophila melanogaster - Kennington, W. Jason (Copyright © 2007 by the Genetics Society of America, 2007)
Associations between genotypes for inversions and quantitative traits have been reported in several organisms, but little has been done to localize regions within inversions controlling variation in these traits. Here, we use an association mapping technique to identify genomic regions controlling variation in wing size within the cosmopolitan inversion In(3R)Payne in Drosophila melanogaster. Previous studies have shown that this inversion strongly influences variation in wing size, a trait highly correlated with body size. We found three alleles from two separate regions within In(3R)Payne with significant additive effects on wing size after the additional effect of the inversion itself had been taken into account. There were also several alleles with significant genotype-by-inversion interaction effects on wing size. None of the alleles tested had a significant additive effect on development time, suggesting different genes control these traits and that clinal patterns in them have therefore arisen independently. The presence of multiple regions within In(3R)Payne controlling size is consistent with the idea that inversions persist in populations because they contain multiple sets of locally adapted alleles, but more work needs to be done to test if they are indeed coadapted.